PACKAGING DESIGN OF FRIED BANANA PRODUCTS FOR FOOD PACKAGING ASSURANCE FOR CONSUMERS USING FOOD DELIVERY SERVICES IN MAKASSAR CITY - Lamatinulu Ahmad; Irma Nur Afiah; Arfandi Ahmad; Muhammad Irfandi; Nurul Chairany (Center for Study and Journal Management FTI UMI, 2022)
The culinary business in Indonesia is increasingly in demand by seeing the increasing number of people who like to hunt for a variety of food menus, both traditional, national, and international food. This is evidenced by the increasing number of culinary businesses that have been established from time to time, including culinary businesses that have developed in Indonesia such as Browcil, JCO, Pizza Hut, Burger King, Kentucky Fried Chicken, and Big Bananas. Big Bananas is one of the most popular culinary food businesses today. He started his business in September 2017 with two types of snacks, namely banana nuggets and banana rolls with flavors ranging from chocolate, and green tea, to vanilla. By joining Big Bananas with online delivery services, namely Gojek and Grab, packaging design must be paid more attention to ensure that these products reach consumers safely. So there is no anxiety for BigBananas consumers and Food Delivery service users, namely problems that often arise for Food Delivery service users such as easy-to-open packaging, no composition information, and no Big Bananas product packaging seal on the packaging which causes consumers to ask- asked about the safety of Big Bananas products to consumers who use Food Delivery services, so the need for a new Big Bananas packaging design to guarantee food safety for consumers using Food Delivery services. So with that Big Bananas’ packaging needs to be redesigned to improve food safety in maintain product quality from the packaging by changing the packaging design, displaying complete attributes on the packaging, changing the color according to product characteristics, providing a seal on the packaging, and selecting the packaging material that is resistant to water and oil so that product quality is maintained and does not cause anxiety to Big Bananas customers in Makassar city